2012
DOI: 10.1007/s10903-011-9566-2
|View full text |Cite
|
Sign up to set email alerts
|

Immigration Disparities in Cardiovascular Disease Risk Factor Awareness

Abstract: Background No previous study has assessed the association between immigration status and awareness regarding a person's own CVD risk factors. Methods Using physical examination-based data and participants' self-report of prior diagnosis, we assessed immigration-based disparities in awareness of diabetes, hypertension, hypercholesterolemia, and overweight among 12,124 participants in the 2003-2008 National Health and Nutritional Survey. Results Unawareness of CVD risk factors is high among all groups, but t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 40 publications
(26 citation statements)
references
References 31 publications
2
24
0
Order By: Relevance
“…As for the disparities in the management of immigrants with cardiovascular diseases, one study found immigrants more likely than patients born in the US to be unaware of their CVD risk factors, and consequently less motivated to seek treatment or modify their behavior to prevent negative CVD outcomes [26]. This is consistent with our finding that immigrants from HMPC with CHD or CHF fared less well in all management indicators and were up to 70% less likely to be taking ACE inhibitors than their Italian counterparts.…”
Section: Discussionmentioning
confidence: 99%
“…As for the disparities in the management of immigrants with cardiovascular diseases, one study found immigrants more likely than patients born in the US to be unaware of their CVD risk factors, and consequently less motivated to seek treatment or modify their behavior to prevent negative CVD outcomes [26]. This is consistent with our finding that immigrants from HMPC with CHD or CHF fared less well in all management indicators and were up to 70% less likely to be taking ACE inhibitors than their Italian counterparts.…”
Section: Discussionmentioning
confidence: 99%
“…First, higher awareness in this population could lead to higher treatment-seeking behavior [53]. A few explanations could be postulated.…”
Section: Discussionmentioning
confidence: 99%
“…Because treatment at emergency departments is available to all immigrants regardless of their status under the Emergency Medical Treatment and Labor Act, the law has had the unintended consequence of discouraging immigrants from seeking primary care in favor of utilizing emergency departments, which is more costly for users and taxpayers. Latino immigrants with limited access—or no access—to a usual source of care tend to delay seeking services and tend to be diagnosed with chronic conditions at a later disease stage or remain unaware of their disease (5, 73, 133), which can result in deteriorating health (19). When these conditions progress unchecked, they are likely to require more aggressive, invasive, and costly interventions as acute treatment becomes necessary, if they are treated at all (155).…”
Section: Health Care Access and Utilization Trends For Latinosmentioning
confidence: 99%